2021
DOI: 10.2147/jep.s262349
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Drugs for Chemotherapy- and Cancer-Related Anemia

Abstract: Anemia in cancer patients is a relevant condition complicating the course of the neoplastic disease. Overall, we distinguish the anemia which arises under chemotherapy as pure adverse event of the toxic effects of the drugs used, and the anemia induced by the tumour-associated inflammation, oxidative stress, and systemic metabolic changes, which can be worsened by the concomitant anticancer treatments. This more properly cancer-related anemia depends on several overlapping mechanism, including impaired erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 152 publications
(223 reference statements)
0
28
0
6
Order By: Relevance
“…Anemia is one of the most usual side effects of chemotherapy drugs, and continuous administration of single-agent 5-FU can cause about 50% of first- and second-degree anemias [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is one of the most usual side effects of chemotherapy drugs, and continuous administration of single-agent 5-FU can cause about 50% of first- and second-degree anemias [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…[6] In clinical practice, cancer-related anemia can be caused by several overlapping mechanisms (e.g., impaired erythropoiesis and chemotherapy-induced loss of appetite). [7][8][9] For a more complete approach, careful evaluation of cancer-related anemia is important.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding to anemia recti cation, blood transfusion, erythropoietin-stimulating agents (ESAs) and iron are three main treatment modalities [32]. Since blood transfusion become more restrictive in mild or moderate anemia after the induction of ESAs, results of clinical trials support the e cacy and safety of ESAs in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has several deleterious effects in patients suffered from malignancy. Several studies have reported a negative impact of anemia on disease progression, response to chemo-/radiotherapy, survival, and risk of death [19,20]. Although anemia may be a consequence of more aggressive forms of cancer, which have worse outcomes, the additional mechanisms unrelated to the tumor may affect prognosis in patients with anemia.…”
Section: Discussionmentioning
confidence: 99%